SNPs within CHRNA5-A3-B4 and CYP2A6/B6 are associated with smoking dependence but not with tobacco dependence treatment outcomes in the Czech population - Hubacek, J A; Pankova, A; Stepankova, L; Zvolska, K; Adamkova, V; Lanska, V; Kralikova, E (Gene, 2017)
PURPOSE: Tobacco/nicotine dependence has a significant heritable component. Genome-wide association studies have associated the single nucleotide polymorphisms (SNPs) rs578776, rs16969968, rs6474412, rs3733829 and rs4105144 with nicotine dependence in Western European populations. We examined whether these SNPs influence nicotine dependence and successful treatment of tobacco dependence in the Czech middle-European population. MATERIALS AND METHODS: Variants were analysed by PCR-RFLP or by TaqMan assay in 807 adult heavy tobacco-dependent smokers - patients of the Centre for Treatment of Tobacco Dependence (Prague) as well as 1,362 self-reported non-smokers. RESULTS AND DISCUSSION: Except for rs3733829, association with tobacco dependence was confirmed for all other genetic variants. In agreement with previous studies, the strongest determinant of tobacco dependence was rs16969968 with OR (95%CI) 1.32 (1.08-1.62) for A allele carriers vs. GG comparison (P=0.003). In contrast, none of the analysed variants reached significance with respect to a 1-year course of successful tobacco dependence treatment (all P over 0.18) in a subset of 525 patients. CONCLUSION: We confirmed the association between variants within genes that code nicotinic-acetylcholine receptors (-A3, -A5 and -B3), CYP2A6/B6 and tobacco dependence development in the Czech population. The success of the tobacco dependence treatment was not influenced by the analysed SNPs.
Keywords: Genetic Predisposition to Disease; celogenomová asociační studie; jednonukleotidový polymorfismus; Czechoslovakia; Československo; mužské pohlaví; EGLN2; Cytochrome P-450 CYP2A6; Adult; Nerve Tissue Proteins; CYP2A6/B6; Smoking cessation; Czechs; ženské pohlaví; nikotinové receptory; Humans; Tobacco Use Disorder; Nicotine-acetylcholine receptors; proteiny nervové tkáně; poruchy vyvolané užíváním tabáku; cytochrom P450 CYP2A6; Receptors, Nicotinic; dospělí; genetická predispozice k nemoci; Female; cytochrom P450 CYP2B6; Cytochrome P-450 CYP2B6; Genome-Wide Association Study; Tobacco dependence; lidé; Male; Polymorphism, Single Nucleotide